RITUAL RUWATAN MURWAKALA DALAM RELIGIUSITAS MASYARAKAT JAWA - Dewi Ayu Wisnu Wardani (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2020)
Ruwatan Murwakala is a ritual tradition that is still preserved by most Javanese people. Javanese society is a society that is rich in treasures and traditions from the ancestors and with this the Javanese people have to maintain Javanese culture. Javanese values ??are stored behind ritual symbols, while some Javanese are no longer able to read and understand the language of these symbols. As a result, Javanese rituals such as Ruwatan Murwakala are increasingly distant from his heir. Ruwatan ceremony is a Javanese traditional ceremony full of meaning. However, explanations and studies that are able to bridge the ritual to the people of Java so far have not understood. The puppet show with the Murwakala play is a depiction of the growth and development of the catastrophe (crime, destruction) and extinction. In order to ward off the threat of the safety of human life, Dalang Kandhabuwana needs to be shown, namely the depiction of Bhatara Vishnu who has the authority to deal with all the disasters waged by Bhatara Kala. Dalang Kandhabuwana is an authorized force and serves as a savior of human life by